Be vigilant before you clamp the cord: iatrogenic transaction of ileum - an avoidable catastrophe - Prakash, Advait; Doshi, Bhavesh; Singh, Sangram; Sanwatsarkar, Sadhna (International Journal of Contemporary Pediatrics, 2016)
Congenital hernia of the umbilical cord (CHUC) is a rare congenital midline abdominal defect as compared to the umbilical hernia which is much more common and occurs post-natally. Despite its recognition as a distinct entity since 1920s, CHUC is often misdiagnosed as a small omphalocele, resulting in its under-reporting. These masses may be easily overlooked at birth, which may result in complications like infections and an intestinal injury due to careless proximal application of the cord clamp. Herein, we present a neonate who sustained accidental transaction of small bowel in congenital hernia of the umbilical cord due to inappropriate clamping of the cord. The case is reported in order to emphasize the potential hazard of clamping the bowel at the time of the handling of the umbilicus. It is imperative that extreme caution should be exercised by medical professionals and nursing staff prior to clamping the cord in order to avoid this type of injury. Such injuries are completely preventable if proper care and utmost precaution is taken during ligation of cord but can result in catastrophes otherwise. For the benefit of the readers the embryology of CHUC and differentiating features from other abdominal wall defects are also discussed.